Charge transport behaviors in epitaxial BiFeO3 thick films sputtered with different Ar/O2 flow ratios. (1st April 2016) - Zhu, Hanfei; Sun, Xin; Kang, Limin; Hong, Mina; Liu, Menglin; Yu, Zhenghai; Ouyang, Jun
Abstract: Heteroepitaxial BiFeO3 thick films were prepared on (100) LaAlO3 substrates using magnetron sputtering. The sputtering atmosphere, i.e. Ar/O2 flow ratio, showed significant influence on the charge transport behaviors of BiFeO3 films. The distinct current density–electric field (J–E) characteristics of films were fitted to three charge transport models: ionic conduction, Schottky emission, and space-charge-limited-current (SCLC). These models were verified by an Auger depth profiling study, which revealed the chemical compositions of the films across their thicknesses. The apparent flow ratio dependence of charge transport in these films is well explained by the models with the supporting Auger data. Graphical abstract: